A translocator-specific export signal establishes the translocator-effector secretion hierarchy that is important for type III secretion system function - Tomalka, Amanda G. (2012)
Type III secretion systems are used by many Gram-negative pathogens to directly deliver effector proteins into the cytoplasm of host cells. To accomplish this, bacteria secrete translocator proteins that form a pore in the host-cell membrane through which the effector proteins are then introduced into the host cell. Evidence from multiple systems indicates that the pore-forming translocator proteins are exported before effectors, but how this secretion hierarchy is established is unclear. Here we used the P. aeruginosa translocator protein PopD as a model to identify its export signals. The amino-terminal secretion signal and chaperone, PcrH, are required for export under all conditions. Two novel signals in PopD, one proximal to the chaperone-binding site and one at the very C-terminus of the protein, are required for export of PopD before effector proteins. These novel export signals establish the translocator-effector secretion hierarchy, which in turn, is critical for the delivery of effectors into host cells.